Pengaruh dukungan sosial terhadap harga diri remaja putri korban pelecehan seksual - Putri Aulia Viskarini; Yudi Suharsono (Fakultas Psikologi, 2023)
Sexual harassment is one of fifteen forms of sexual violence that have occurred in Indonesia. Sexual harassment has a long-term negative impact in the form of low self-esteem. One of the factors that can affect self-esteem is social support from the environment. Adolescence is often associated with fluctuations in self-esteem because of the changes in individual’s way of thinking which are often influenced by the environment at this age. This research aims to see the effect of social support on female adolescent victims of sexual harassment on self-esteem. Sexual harassment in this study is specified in public space sexual harassment that occurs in public spaces. This study uses quantitative approach. Researcher used purposive sampling technique on adolescents aged 14-24 years who had experienced sexual harassment and had told their family, friends, and/or significant others about this experience. The instruments used in this study were Septian's (2018) Self Esteem Scale and modified Social Support Scale from Zimet's (1988) MSPSS Scale. After using regression analysis it was found that social support had a positive effect on self-esteem with a number of (r = 0.070, p <0.05) which means that the higher the social support that adolescent women get after telling their experiences of sexual harassment, the higher their self-esteem will be after sexual harassment and vice versa. Keywords: Public sexual harassment, self esteem, social support